Patterns of use of dry powder inhalers versus pressurized metered-dose inhalers devices in adult patients with chronic obstructive pulmonary disease or asthma: - Ramadan, Wijdan H. (2017)
Numerous patients with chronic obstructive pulmonary disease (COPD) and asthma do not use inhaler devices properly, which can contribute to poor disease control. The objective of this study is to assess the technical and safety use of dry powder inhalers (DPIs) versus pressurized metered-dose inhalers (MDIs) in adult patients with COPD or asthma in Lebanon. A concurrent, prospective comparative observational study was conducted at one hospital and 15 community pharmacies in Lebanon. Over a period of 18 months, 246 questionnaires were filled. Patients included were adults with COPD or asthma. Answers were entered into the Statistical Package for Social Sciences software and excel sheet. T-test and correlation were used to analyze the results; 67.8% and 38.4% of those using DPIs and MDIs, respectively, performed the exact technical steps adequately (p = 0.003, relative risk: 2.134, 95% confidence interval: 0.910–4.842). When compared to MDI, a higher percentage of DPI users found their devices easy to use. Moreover, 81.4% of the MDI users found difficulty in coordinating between pressing the canister and inhaling. Rates of exacerbations were significantly higher in MDIs vs. DPI users (59.4% vs. 21.7%). Overall, 44.31% of patients did not receive education from their healthcare professionals about the devices. A significant number of COPD/asthma adult patients do not use their devices properly. Even though DPIs were significantly easier to use, proper education on the technical use of all types of inhalers is needed.